2020
DOI: 10.1007/s40336-020-00393-x
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of the roots of the brachial plexus: a systematic review and meta-analysis of normative values

Abstract: Purpose Diffusion tensor magnetic resonance imaging (DTI) characterises tissue microstructure and provides proxy measures of myelination, axon diameter, fibre density and organisation. This may be valuable in the assessment of the roots of the brachial plexus in health and disease. Therefore, there is a need to define the normal DTI values. Methods The literature was systematically searched for studies of asymptomatic adults who underwent DTI of the brachial plexus. Participant characteristics, scanning prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
(93 reference statements)
3
5
0
Order By: Relevance
“…Although our findings are in agreement with the metrics reported in many DTI studies of the brachial plexus 4 7 , 9 , 10 , 26 (Supplementary Table 2 ), our FA values are slightly lower. FA is a function of numerous factors such as the b-value and number of diffusion encoding directions 27 , 28 .…”
Section: Discussionsupporting
confidence: 92%
“…Although our findings are in agreement with the metrics reported in many DTI studies of the brachial plexus 4 7 , 9 , 10 , 26 (Supplementary Table 2 ), our FA values are slightly lower. FA is a function of numerous factors such as the b-value and number of diffusion encoding directions 27 , 28 .…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies in the brain have shown dMRI metrics and streamlines to be dependent on scanner hardware, acquisition settings, preprocessing techniques, reconstruction algorithms and extraction methods 2,[9][10][11][12][13][14] . Recent work has shown similar dependence in the brachial plexus 15 and median nerve in the hand 16 . Therefore, before researchers and clinicians can reliably use dMRI to assess the 'health' of the major nerves of the upper limb, there is a need to de ne the range of "normal" values and how they vary with experimental conditions.…”
Section: Introductionmentioning
confidence: 78%
“…However, the proximity of peripheral nerves and skeletal muscles, similar FA values of both tissues, spatial resolution, algorithm type, different ROIs sizes, numbers and locations of the ROIs ( 40 ) may cause contamination by skeletal muscle fibers (e.g., scalene muscles), when MRT of the BP nerve bundles is performed.…”
Section: Discussionmentioning
confidence: 99%